Shear bond strength of metallic and ceramic brackets using color change adhesives - Aisha de Souza Gomes Stumpf; Carlos Bergmann; José Renato Prietsch; Juliane Vicenzi (Dental Press Editora, 2013)
OBJECTIVE: To determine the shear bond strength of orthodontic brackets using color change adhesives that are supposed to aid in removing excess of bonding material and compare them to a traditional adhesive. METHODS: Ninety metallic and ninety ceramic brackets were bonded to bovine incisors using two color change adhesives and a regular one. A tensile stress was applied by a universal testing machine. The teeth were observed in a microscope after debonding in order to determine the Adhesive Remnant Index (ARI). RESULTS: The statistical analysis (ANOVA, Tukey, and Kruskall-Wallis tests) demonstrated that the mean bond strength presented no difference when metallic and ceramic brackets were compared but the bond resistance values were significantly different for the three adhesives used. The most common ARI outcome was the entire adhesive remaining on the enamel. CONCLUSIONS: The bond strength was similar for metallic and ceramic brackets when the same adhesive system was used. ARI scores demonstrated that bonding with these adhesives is safe even when ceramic brackets were used. On the other hand, bond strength was too low for orthodontic purposes when Ortho Lite Cure was used.